Effects of GDI injector deposits on spray and combustion characteristics under different injection conditions. (15th October 2020) - Zhang, Zhou; Zhang, Wenbin; Ma, Xiao; Awad, Omar I.; Xu, Hongming; Shuai, Shijin
Abstract: Injector deposits, which deteriorate the combustion and emissions, are frequent in gasoline direction injection (GDI) engines. An objective of this paper was to investigate the effects of the GDI injector deposits on the spray and combustion characteristics in a constant volume chamber (CVC) and an optical GDI engine, respectively, using different fuel temperature, injection pressure, and injection strategies. The spray and tail droplet characteristics were analyzed by using high-speed imaging. The combustion characteristics involving flame propagation, diffusion flame, and particle emissions were studied in a single-cylinder optical GDI engine. The results showed that the deposits slightly increased the spray penetration at 30 °C, and the deposits enhanced the flash-boiling process at the fuel temperatures of 60 °C and 90 °C. The influence of the deposits on flash-boiling was weakened at 20 MPa injection pressure. Compared with the clean injector, the fouled injector had smaller and lower speed tail droplets, slightly lower combustion flame speed, and slightly smaller peak in-cylinder pressure. Moreover, the fouled injector had much more tip diffusion flame compared with the clean injector. The split injection strategy increased the tip diffusion flame and soot emission for both injectors at a fuel temperature of 90 °C. The diffusion flame luminance was linear with the number concentration of accumulation mode particles, and the luminance of the diffusion flame can characterize the soot concentration. The tip diffusion flame caused by the deposits is the primary source of soot emission at a fuel temperature of 90 °C.